Nitrogen-doped graphene guided formation of monodisperse microspheres of LiFePO4 nanoplates as the positive electrode material of lithium-ion batteries - Zhou, Yingke; Lu, Jiming; Deng, Chengji; Zhu, Hongxi; Chen, George Z.; Zhang, Shaowei; Tian, Xiaohui (Royal Society of Chemistry, 2016)
Three-dimensional porous composite microspheres of LiFePO4 and nitrogen doped graphene have been synthesized by a solvothermal process coupled with subsequent calcination. The morphologies and microstructures of the composites are investigated by scanning electron microscopy, X-ray diffraction, transmission electron microscopy and X-ray photoelectron spectroscopy. The electrochemical properties are evaluated by constant current charge/discharge tests, cyclic voltammetry and electrochemical impedance spectroscopy. The unique porous structure of the microspheres is constructed by the assembly of nitrogen-doped graphene and LiFePO4 nanoplates, and can remarkably enlarge the electrode/electrolyte interface area, facilitate the electron transfer process, shorten the ionic diffusion path and accelerate the ionic transport throughout the electrode. In electrochemical measurements of specific charge capacity, rate capability and cycling stability, the obtained porous composite microsphere materials offer remarkably promising results for application in high-performance lithium-ion power batteries.